Olympic Weightlifting Training for Sprint Performance in Athletes: A Systematic Review with Meta-analysis - Crenshaw, Kristen; Zeppieri, Giorgio; Hung, Cheng-Ju; Schmitfranz, Tania; McCall, Patti; Castellini, Greta; Gianola, Silvia; Pozzi, Federico (International Journal of Sports Medicine, 2024)
This systematic review and meta-analysis aimed to determine whether Olympic weightlifting (OW) exercises would improve sprint performance when compared to a control intervention, (no training, standard sport-specific training, traditional resistance training, or plyometric training). Medline, Web of Science, SportDiscus, CINAHL, and Biological Science from inception to September 2022 was searched. Two authors independently selected the included studies, extracted data, and appraised the risk of bias. Certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation methodology. The primary meta-analysis combined the results of the sprint performance over the full length of each sprint test. The secondary meta-analyses combined the results of the sprint performance at 5, 10, and 20 m distance to capture information about the acceleration phase of the sprint tests. Eight studies with 206 athletes (female n=10, age range: 18.9–24.2 years) were identified. Sprint performance did not differ significantly comparing OW to the control intervention, nor at the full length (standardized mean difference=–0.07, 95% CI=–0.47 to 0.34, p=0.75, I2=46%) or during the acceleration phase (p≥0.26) of the sprint test. OW training does not improve sprint performance to a greater extent than comparator interventions.
Keywords: olympic weightlifting; sprint; athletes; training